Determining the habitat fragmentation thru geoscience capabilities in Turkey: A case study of wildlife refuges - ALTUNEL, Arif Oğuz; ÇAĞLAR, Sadık; AÇIKGÖZ ALTUNEL, Tayyibe (International Journal of Engineering and Geoscience, 2021)
Technical forest management started 180 years ago in Turkey, during which time there have been various approaches and policy changes. The primary objective of forestry has been considered as timber production, so the intangible benefits have never been given the proper attention they deserve. The majority of Turkey’s wildlife has prospered within the forest ecosystems. This situation has gradually led to a change of status, so some forests and land areas have been reassigned with the conservation agendas as the primary purpose; however timber production has never slowed down. Thus, operational forestry practices, such as roading, logging, etc., have kept on exploiting these lands to their full extent despite their conservation statuses. In Turkey and anywhere else, since forestry has always evolved around extracting the timber out of the forest lands, the accessibility has long been provided, building roads to take related services to forested ecosystems. The remnants of these roads, along with the more standardized new ones can be found everywhere, regardless of the land status. Such expansion has resulted in habitat fragmentation emerging as a major threat for the protected areas. In this study, the expansion of all-weather and dry-weather accessible roads and suburban spread was examined in two adjacent, Ilgaz and Gavurdagi, wildlife refuges for the years of 1960, 1993, 2010 and 2019, relying heavily on the mapping, geographic information systems (GIS) and remote sensing. It was found that 275.5 km dry-weather roads in 1960 rose to 700 km in 2017, which meant 254% increase. Additionally, when the core along with the surrounding 3000 m buffer area was considered, 51 km all-weather roads in 1960 increased almost four and a half times by 2019. Suburban expansion was relatively stable inside the core area but had almost quadrupled within the surrounding areas, exposing the refuges to more people. These findings indicated that the wildlife habitats of Turkey are fragmented and under heavy human pressure.
Keywords: Fragmentation; Roading; Suburban expansion; Geographic Information Systems; Landsat; 11. Sustainability; 15. Life on land